Novel carbide high-entropy ceramic and preparation method thereof

By adding metal Ti to the high entropy carbide ceramic system to synthesize C vacancy, the problems of high sintering temperature and low toughness are solved, efficient sintering and performance improvement are achieved, and suitable for industrial production.

CN119710415APending Publication Date: 2025-03-28YANSHAN UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510037034.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing high-entropy carbide ceramic materials have high sintering temperature and low toughness, making it difficult to meet the needs of high-performance materials.

Method used

C vacancy was synthesized in situ by adding metal Ti to (Ti, V, Nb, Zr)C and (Ti, V, Nb, Zr, Ta, Hf)C high-entropy carbide systems, and a new high-entropy ceramic was prepared by mechanical alloying and SPS sintering processes.

Benefits of technology

It reduces the sintering temperature, improves the toughness of the material, and has a simple process, short time and low cost, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710415A_ABST
    Figure CN119710415A_ABST
Patent Text Reader

Abstract

The invention provides a novel carbide high-entropy ceramic and a preparation method thereof, the novel carbide high-entropy ceramic material is prepared from TiC, VC, NbC, ZrC, TaC, HfC metal carbides and metal Ti powder as raw materials, the molar ratio of TiC: VC: NbC: ZrC: Ti is 1: 1: 1: 1: 1: x (x = 1, 2.5), and the molar ratio of TiC: VC: NbC: ZrC: TaC: HfC: Ti is 1: 1: 1: 1: 1: 1: x (x = 1, 2.5, 3.5). Preparing mixed powder before sintering by adopting a mechanical alloying method; the mixed powder is put into a mold to be pre-pressed; and sintering the pre-pressed sample by adopting a spark plasma sintering process to prepare the novel carbide high-entropy ceramic material. According to the research, a C vacancy is generated in situ in a high-entropy carbide ceramic system by adding metal Ti, so that the solid solution temperature and the sintering temperature of the high-entropy ceramic material are effectively reduced, and the toughness of the high-entropy ceramic material is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high entropy ceramic materials, and in particular to a novel carbide high entropy ceramic and a preparation method thereof. Background Art

[0002] As one of the ultra-high temperature ceramics, refractory metal carbides have extremely high melting temperatures, high temperature phase stability, superior corrosion resistance and chemical stability, high hardness and good wear resistance. They can be used in supersonic aircraft, rocket engines and high temperature resistant materials in the metallurgical industry, and wear-resistant parts such as cutting tools and drills in the military industry. With the development of the times, materials with higher performance are needed in the fields of engines, cutting tools, nuclear equipment, etc. In recent years, studies have shown that with the help of the "high entropy" concept in high entropy alloys, the solid solution effect in high entropy materials can integrate the characteristics of each component, and high entropy carbide ceramics are expected to show better performance. The common raw materials for the preparation of high entropy carbide ceramic powders are the following three: metal carbides, metal powder / carbon, metal oxide / carbon, and they are prepared by mechanical alloying, carbon thermal reduction, molten salt and other methods. The most commonly used method for bulk preparation is spark plasma sintering (SPS). In addition, there are also methods such as hot pressing sintering, vacuum sintering, high pressure sintering and gas pressure sintering. Since transition metal carbides are all high melting point, low toughness materials, and the high entropy effect has no obvious improvement effect on the toughness of the materials, the current high entropy carbide ceramics still have shortcomings such as high sintering temperature and low toughness.

[0003] Wang Dafei et al. used metal oxides and carbon powder as raw materials, and then prepared three kinds of quaternary high entropy ceramic materials (Ti, Nb, Ta, Mo)C, (Ti, Nb, Ta, W)C, and (Ti, Nb, Ta, V)C by SPS process at 1850 ℃ after high-energy ball milling. The results show that the three carbide ceramics are all single-phase FCC structures; the molybdenum-containing ceramic has the finest grains and the least pores. Due to the complete densification of the organization and the uneven distribution of components, the flexural strength of the three ceramics is lower than expected. Among the three ceramics, (Ti, Nb, Ta, W)C has the best comprehensive performance, with a hardness of 20.6 GPa and a flexural strength of 393 MPa [Wang Dafei, Liu Ning, Zhang Xiaoling, et al. Study on the organization and properties of quaternary high entropy carbide ceramics [J]. Heat Treatment, 2020, 35(2): 8-12.]. Chen Jingjing et al. successfully prepared (Ti) by SPS process on carbide powder. 0.25 Zr 0.25 Nb 0.25 Ta 0.25)C high entropy ceramics. The results show that the formation temperature of single-phase high entropy ceramics is 1800 ℃. The ceramics sintered at 1900 ℃ have fine grains, an average grain size of about 7.5 µm, uniform element distribution, and a relative density of up to 99.2%. The room temperature microhardness values ​​of high entropy ceramics sintered at 1800 ℃ and 1900 ℃ are 30.9 GPa and 33.2 GPa, respectively, and the fracture toughness is (4.6±0.24) MPa·m 1 / 2 and (4.5±0.31)MPa·m 1 / 2 [Chen Jingjing, Huang Zhangyi, Qi Jianqi, et al. (Ti 0.25 Zr 0.25 Nb 0.25 Ta 0.25 )C high entropy ceramics[J]. Bulletin of the Silicate Society, 2022.] Yu Duo used metal carbide powder as raw material to prepare (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )C high entropy ceramics, the raw material powders were mixed by ball milling, and the sintered body was prepared by SPS sintering process, with a heating rate of 100 ℃ / min, a sintering temperature of 1900 ℃, a sintering pressure of 40 MPa and 60 MPa respectively, and a holding time of 5 min. The study showed that the phase composition of the sintered body was a single solid solution phase, and the best performance of the sintered body was a hardness of 19 GPa and a toughness of 3 MPa·m 1 / 2 [Yu Duo. (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )C Study on sintering densification and properties of high entropy ceramics [D]. Shanghai: Shanghai Institute of Ceramics, Chinese Academy of Sciences, 2021.]. The raw materials used in the above research on high entropy ceramic materials are all stoichiometric metal compounds with equal molar ratios. The preparation of sintered bodies requires a higher sintering temperature (1800~1900 ℃). The phase composition of the sintered bodies is a single solid solution phase. The toughness of the obtained high entropy ceramic materials is relatively low, 3-5 MPa·m 1 / 2 about.

[0004] In order to reduce the sintering temperature of high entropy ceramic materials and improve their toughness, some researchers chose to prepare high entropy ceramics with non-stoichiometric metal compounds as one of the components. Liu Bingsai et al. first used mechanical alloying to prepare non-stoichiometric TiC 0.5 , using it as one of the metal carbide components to prepare TiC 0.5 -VC-NbC, TiC 0.5-VC-NbC-TiN, TiC 0.5 -VC-NbC-TiN-TaC three kinds of high entropy ceramic materials. Studies have shown that when the sintering temperature is 1600 ℃, the above three high entropy ceramic sintered bodies contain only a single solid solution phase, while the high entropy ceramics with stoichiometric TiC cannot synthesize a single solid solution phase. Among them, the five-component high entropy ceramic has a fracture toughness of 7.74 MPa·m at 1800 ℃. 1 / 2 , with a hardness of 23.4 GPa [Liu Bingsai, Chen Chuan, Wu Yi, et al. Synthesis of C vacancy-induced diffusion-type high-entropy ceramic hard materials [J]. Superhard Materials Engineering, 2020, 32(5): 30-38.]. He Wenquan prepared non-stoichiometric TiC by mechanical alloying. 0.4 As one of the components, a hardness of 23 GPa and a toughness of 6 MPa·m were prepared at 1600-1700 ℃. 1 / 2 WC-TiC 0.4 -VC, WC-TiC 0.4 -NbC, WC-TiC 0.4 -TaC ternary medium entropy ceramics and WC-TiC 0.4 -VC-NbC quaternary high entropy ceramics [He Wenquan. Synthesis and performance research of new ceramic binder WC cemented carbide materials [D]. Qinhuangdao: Yanshan University, 2019.]. Peng Chong used non-stoichiometric metal compounds TiN 0.3 TiN prepared at 1300 °C 0.3 -VC-NbC-TiC-TaC-Mo 2 The toughness of C-WC high entropy ceramic material reaches 8.4 MPa·m 1 / 2 [Peng Chong. Effect of carbon (nitrogen) vacancies on the formation and properties of entropy-stabilized compounds[D]. Qinhuangdao: Yanshan University, 2021.]. The above research results show that the introduction of vacancy defects can promote the formation of single-phase high-entropy ceramic materials and can also improve the toughness of high-entropy ceramic materials to a certain extent.

[0005] Based on the above research, high entropy ceramic materials prepared with stoichiometric metal compounds have shortcomings such as high sintering temperature and low toughness. Although the sintering temperature of high entropy ceramic materials is reduced and their toughness is improved by adding non-stoichiometric metal compounds to introduce vacancy defects, the preparation process of non-stoichiometric compounds is complex, time-consuming and costly. In order to make high entropy ceramic materials meet the requirements of scientific and technological development for materials in terms of production, preparation and performance, it is urgent to develop new methods to improve their shortcomings of high sintering temperature and low toughness. Summary of the invention

[0006] According to the above-mentioned shortcomings of high sintering temperature and low toughness of high entropy carbide ceramic materials, a new type of carbide high entropy ceramic material and its preparation method are provided. The present invention uses metal Ti as an additive, adds it to (Ti, V, Nb, Zr)C and (Ti, V, Nb, Zr, Ta, Hf)C high entropy carbide systems to synthesize C vacancies in situ, adopts a mechanical alloying method to prepare the mixed powder, and prepares the sintered body by SPS sintering process.

[0007] The technical means adopted by the present invention are as follows: a new type of high-entropy carbide ceramic material, the high-entropy ceramic is designed with a molar ratio of TiC:VC:NbC:ZrC:Ti=1:1:1:1:x(x=1,2.5), TiC:VC:NbC:ZrC:TaC:HfC:Ti=1:1:1:1::1:1:x(x=1, 2.5,3.5).

[0008] The present invention also discloses a method for preparing the novel high entropy carbide ceramic material, which is characterized by comprising the following steps: S1. Preparation of mixed powders: In an argon-filled glove box, raw materials TiC, VC, NbC, ZrC, TaC, HfC and Ti powder were mixed in a WC carbide ball mill at a molar ratio of TiC:VC:NbC:ZrC:Ti=1:1:1:1:x(x=1, 2.5) and TiC:VC:NbC:ZrC:TaC:HfC:Ti=1:1:1:1:1:1:x(x=1, 2.5, 3.5), with a ball-to-material mass ratio of 20:1. The rotation speed was 450 r / min, and the ball milling time was 10-30 h. The mill was stopped for 30 min every 1 h to dissipate heat. The raw materials stuck to the grinding balls and the inner wall of the mill were scraped off and mixed every 10 h, and then ball milling was continued to obtain high entropy carbide mixed powders.

[0009] S2, sintering preparation: the mixed material of step S1 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 30 MPa, and the pre-compression is 60 s; then spark plasma sintering is carried out, the vacuum degree is 40 Pa, the sintering pressure is 40 MPa, the sintering temperature is 1500-1800 ℃, the heating rate is 100 ℃ / min, and the holding time is 10 min; then the temperature is reduced and the pressure is released to obtain a new type of high entropy ceramic.

[0010] Furthermore, the purity of the TiC, VC, NbC, ZrC, TaC, HfC and Ti powders is greater than 99.5%, and the particle sizes are all 1 to 3 μm.

[0011] Furthermore, in the ball milling process in step S1, three large, medium and small sizes of WC cemented carbide balls with diameters of 8 mm, 5 mm and 2 mm are used, wherein the mass ratio of the large, medium and small sizes of WC cemented carbide balls is 6:3:1.

[0012] Furthermore, the specific sintering process in step S2 is: first, slowly apply pressure to the sample to 40 MPa; then, evacuate to 40 Pa; then, heat from room temperature to 600 ° C in 5 minutes, and keep at 600 ° C for 10 minutes; then heat from 600 ° C to the final sintering temperature at a heating rate of 100 ° C / min, and keep for 10 minutes; cool with the furnace to obtain a blank; the prepared blank is subjected to surface grinding and deburring treatment to obtain a new type of high entropy ceramic.

[0013] Compared with the prior art, the present invention has the following advantages: 1. The present invention synthesizes C vacancies in situ by adding metal Ti to (Ti, V, Nb, Zr)C and (Ti, V, Nb, Zr, Ta, Hf)C high entropy carbides. The introduction of C vacancies causes a C concentration gradient to appear in the metal carbide system, increases the mutual diffusion coefficient of metal atoms, and reduces the diffusion activation energy. Therefore, the addition of metal Ti can increase the solid solubility of high entropy carbide high entropy ceramics and reduce the sintering temperature.

[0014] 2. The present invention obtains a new type of high-entropy ceramic material with high toughness. The introduction of vacancies will produce a new bonding mode in the metal carbide system: metal-vacancy-metal bond, which increases the metallicity of the system, thereby promoting the plastic deformation of the material, weakening and dispersing the stress at the crack tip, and improving the toughness of the material. In addition, the addition of metal Ti introduces more O elements into the (Ti, V, Nb, Zr)C and (Ti, V, Nb, Zr, Ta, Hf)C systems, and the formation of oxides further improves the toughness of high-entropy ceramics.

[0015] 3. Compared with the method of introducing vacancies by adding non-stoichiometric metal compounds, the method of in-situ synthesis of vacancies by adding metal elements is simpler, less time-consuming, and less costly, and is more suitable for industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor.

[0017] Figure 1XRD diagrams of the novel high entropy ceramics provided by the present invention: (a) XRD diagram of the high entropy ceramic in Example 1; (b) XRD diagram of the high entropy ceramic in Example 2; (c) XRD diagram of the high entropy ceramic in Example 3.

[0018] Figure 2 FESEM images of the high entropy ceramic provided by the present invention: (a) FESEM image of the surface of the high entropy ceramic in Example 7; (b) FESEM image of the fracture of the high entropy ceramic in Example 7. DETAILED DESCRIPTION

[0019] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0020] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0022] Unless otherwise specifically stated, the relative arrangement of the parts and steps described in these embodiments, the numerical expressions and numerical values ​​do not limit the scope of the present invention. At the same time, it should be clear that, for ease of description, the sizes of the various parts shown in the drawings are not drawn according to the actual proportional relationship. The technology, methods and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but in appropriate cases, the technology, methods and equipment should be regarded as part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar numbers and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further discussed in subsequent drawings.

[0023] The present invention provides a novel high entropy ceramic, wherein the molar ratio of the high entropy carbide ceramic material is: TiC:VC:NbC:ZrC:Ti=1:1:1:1:x(x=1, 2.5), TiC:VC:NbC:ZrC:TaC:HfC:Ti=1:1:1:1:1:1:x(x=1,2.5, 3.5). The purity of the TiC, VC, NbC, ZrC, TaC, HfC and Ti powders is greater than 99.5%, and the particle size is 1-3 μm.

[0024] The detection equipment described in the present invention are all instruments used in conventional detection means, such as X-ray diffractometer, hardness tester, scanning electron microscope, etc. Example 1

[0025] Table 1 shows the raw materials and their mass ratios for preparing (Ti, V, Nb, Zr)C-1Ti high entropy ceramics.

[0026]

[0027] S1. Prepare (Ti, V, Nb, Zr)C-1Ti mixed powder according to the raw material molar ratio of TiC:VC:NbC:ZrC:Ti=1:1:1:1:1. In a glove box filled with argon, 1.581 g TiC, 1.662 g VC, 2.769 gNbC, 2.725 g ZrC and 1.263 g Ti were mixed and loaded into a WC cemented carbide ball mill. The ball-to-material mass ratio was 20:1, the rotation speed was 450 r / min, the ball milling time was 10 h, and the mill was stopped for 30 min for heat dissipation every 1 h to obtain (Ti, V, Nb, Zr)C mixed powder.

[0028] S2. First, the mixture was loaded into a graphite mold for pre-pressing at a pre-pressing pressure of 30 MPa for 60 s; then, the vacuum was evacuated to 40 Pa and the pressure was increased to 40 MPa; then, it was heated from room temperature to 600 °C in 5 min and kept at 600 °C for 10 min; then, it was heated from 600 °C to 1600 °C at a heating rate of 100 °C / min and kept at this temperature for 10 min. The mixture was cooled in the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain (Ti, V, Nb, Zr)C-1Ti high entropy ceramics.

[0029] The (Ti, V, Nb, Zr)C-1Ti high entropy ceramic sample was ground and polished for microstructure and performance testing. The density was 98.9%, the hardness was 20.3 GPa, and the toughness was 7.0 MPa m 1 / 2 . Example 2

[0030] The raw materials and their mass ratios in Table 1 were used to prepare (Ti, V, Nb, Zr)C-1Ti high entropy ceramics, and the sintering temperature was adjusted.

[0031] S1. Prepare (Ti, V, Nb, Zr)C-1Ti mixed powder according to the raw material molar ratio of TiC:VC:NbC:ZrC:Ti=1:1:1:1:1. In a glove box filled with argon, 1.581 g TiC, 1.662 g VC, 2.769 gNbC, 2.725 g ZrC and 1.263 g Ti were mixed and loaded into a WC cemented carbide ball mill. The ball-to-material mass ratio was 20:1, the rotation speed was 450 r / min, the ball milling time was 10 h, and the mill was stopped for 30 min every 1 h to dissipate heat, and the (Ti, V, Nb, Zr)C-1Ti mixed powder was obtained.

[0032] S2. First, the mixture was loaded into a graphite mold for pre-pressing at a pre-pressing pressure of 30 MPa for 60 s; then, the vacuum was evacuated to 40 Pa and the pressure was increased to 40 MPa; then, it was heated from room temperature to 600 °C in 5 min and kept at 600 °C for 10 min; then, it was heated from 600 °C to 1700 °C at a heating rate of 100 °C / min and kept at this temperature for 10 min. The mixture was cooled in the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain (Ti, V, Nb, Zr)C-1Ti high entropy ceramics.

[0033] The (Ti, V, Nb, Zr)C-1Ti high entropy ceramic sample was polished and then its structure and performance were tested. The density was 98.6%, the hardness was 21.8 GPa, and the toughness was 6.8 MPa m 1 / 2 . Example 3

[0034] The raw materials and their mass ratios listed in Table 1 were used to prepare (Ti, V, Nb, Zr)C-1Ti high entropy ceramics, and the mechanical alloying time and sintering temperature were adjusted.

[0035] S1. Prepare (Ti, V, Nb, Zr)C-1Ti mixed powder according to the raw material molar ratio of TiC:VC:NbC:ZrC:Ti=1:1:1:1:1. In a glove box filled with argon, 1.581g TiC, 1.662g VC, 2.769g NbC, 2.725g ZrC and 1.263g Ti were mixed and loaded into a WC cemented carbide ball mill. The ball-to-material mass ratio was 20:1, the rotation speed was 450 r / min, the ball milling time was 30 h, and the mill was stopped for 30 min every 1 h to dissipate heat, and the (Ti, V, Nb, Zr)C-1Ti mixed powder was obtained.

[0036] S2. First, the mixture was loaded into a graphite mold for pre-pressing at a pre-pressing pressure of 30 MPa for 60 s; then, the vacuum was evacuated to 40 Pa and the pressure was increased to 40 MPa; then, it was heated from room temperature to 600 °C in 5 min and kept at 600 °C for 10 min; then, it was heated from 600 °C to 1600 °C at a heating rate of 100 °C / min and kept at this temperature for 10 min. The mixture was cooled in the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain (Ti, V, Nb, Zr)C-1Ti high entropy ceramics.

[0037] The (Ti, V, Nb, Zr)C-1Ti high entropy ceramic sample was ground and polished for microstructure and performance testing. The density was 99%, the hardness was 20.7 GPa, and the toughness was 6.4 MPa m 1 / 2 . Example 4

[0038] Table 2 shows the raw materials and their mass ratios for preparing (Ti, V, Nb, Zr)C-2.5Ti high entropy ceramics.

[0039]

[0040] S1. Prepare (Ti, V, Nb, Zr)C-2.5Ti mixed powder according to the raw material molar ratio of TiC:VC:NbC:ZrC:Ti=1:1:1:1:2.5. In a glove box filled with argon, 1.33 g TiC, 1.4 g VC, 2.33 g NbC, 2.29 g ZrC and 2.65 g Ti were mixed and loaded into a WC carbide ball mill. The ball-to-material mass ratio was 20:1, the rotation speed was 450 r / min, the ball milling time was 30 h, and the mill was stopped for 30 min every 1 h to dissipate heat, and the (Ti, V, Nb, Zr)C-2.5Ti mixed powder was obtained.

[0041] S2. First, the mixture was loaded into a graphite mold for pre-pressing at a pre-pressing pressure of 30 MPa for 60 s; then, the vacuum was evacuated to 40 Pa and the pressure was increased to 40 MPa; then, it was heated from room temperature to 600 °C in 5 min and kept at 600 °C for 10 min; then, it was heated from 600 °C to 1700 °C at a heating rate of 100 °C / min and kept at this temperature for 10 min. The mixture was cooled in the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain (Ti, V, Nb, Zr)C-2.5Ti high entropy ceramics.

[0042] The (Ti, V, Nb, Zr)C-2.5Ti high entropy ceramic sample was polished and then its structure and performance were tested. The density was 99.4%, the hardness was 20.3 GPa, and the toughness was 6.3 MPa m 1 / 2 . Example 5

[0043] Table 3 shows the raw materials and their mass ratios for preparing (TiVNbZrTaHf)C-1Ti high entropy ceramics.

[0044]

[0045] S1. Prepare (Ti, V, Nb, Zr, Ta, Hf) C-1Ti mixed powder according to the raw material molar ratio of TiC: VC: NbC: ZrC: TaC: HfC: Ti = 1:1:1:1:1:1:1. In a glove box filled with argon, 0.785 g TiC, 0.825 g VC, 1.374 g NbC, 1.352 g ZrC, 2.541 g TaC, 2.496 g HfC and 0.627 g Ti were mixed and loaded into a WC carbide ball mill. The ball-to-material mass ratio was 20:1, the rotation speed was 450 r / min, the ball milling time was 10 h, and the mill was stopped for 30 min for heat dissipation every 1 h to obtain (Ti, V, Nb, Zr, Ta, Hf) C-1Ti mixed powder.

[0046] S2. First, the mixture was loaded into a graphite mold for pre-pressing at a pre-pressing pressure of 30 MPa for 60 s; then, the vacuum was evacuated to 40 Pa and the pressure was increased to 40 MPa; then, it was heated from room temperature to 600 °C in 5 min and kept at 600 °C for 10 min; then, it was heated from 600 °C to 1600 °C at a heating rate of 100 °C / min and kept at this temperature for 10 min. The mixture was cooled in the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain (Ti, V, Nb, Zr, Ta, Hf)C-1Ti high entropy ceramics.

[0047] The (Ti, V, Nb, Zr, Ta, Hf)C-1Ti high entropy ceramic sample was ground and polished for microstructure and performance testing. The density was 96.9%, the hardness was 21.9 GPa, and the toughness was 5.5 MPa m 1 / 2 . Example 6

[0048] The raw materials and their mass ratios in Table 3 were used to prepare (TiVNbZrTaHf)C-1Ti high entropy ceramics, and the mechanical alloying time was adjusted: S1. Prepare (Ti, V, Nb, Zr, Ta, Hf) C-1Ti mixed powder according to the raw material molar ratio of TiC: VC: NbC: ZrC: TaC: HfC: Ti = 1:1:1:1:1:1:1. In a glove box filled with argon, 0.785 g TiC, 0.825 g VC, 1.374 g NbC, 1.352 g ZrC, 2.541 g TaC, 2.496 g HfC and 0.627 g Ti were mixed and loaded into a WC carbide ball mill. The ball-to-material mass ratio was 20:1, the rotation speed was 450 r / min, the ball milling time was 30 h, and the mill was stopped for 30 min for heat dissipation every 1 h to obtain (Ti, V, Nb, Zr, Ta, Hf) C-1Ti mixed powder.

[0049] S2. First, the mixture was loaded into a graphite mold for pre-pressing at a pre-pressing pressure of 30 MPa for 60 s; then, the vacuum was evacuated to 40 Pa and the pressure was increased to 40 MPa; then, it was heated from room temperature to 600 °C in 5 min and kept at 600 °C for 10 min; then, it was heated from 600 °C to 1600 °C at a heating rate of 100 °C / min and kept at this temperature for 10 min. The mixture was cooled in the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain (Ti, V, Nb, Zr, Ta, Hf)C-1Ti high entropy ceramics.

[0050] The (TiVNbZrTaHf)C-1Ti high entropy ceramic sample was polished and then its microstructure and performance were tested. The density was 97.5%, the hardness was 23.2 GPa, and the toughness was 5.3 MPa m 1 / 2 . Example 7

[0051] Table 4 shows the raw materials and their mass ratios for preparing (TiVNbZrTaHf)C-3.5Ti.

[0052]

[0053] S1. Prepare (Ti, V, Nb, Zr, Ta, Hf) C-1Ti mixed powder according to the raw material molar ratio of TiC: VC: NbC: ZrC: TaC: HfC: Ti = 1: 1: 1: 1: 1: 3.5. In a glove box filled with argon, the raw materials 0.68 g TiC, 0.71 g VC, 1.19 g NbC, 1.17 g ZrC, 2.19 g TaC, 2.16 g HfC and 1.9 g Ti were mixed and loaded into a WC carbide ball mill. The ball-to-material mass ratio was 20: 1, the rotation speed was 450 r / min, the ball milling time was 30 h, and the machine was stopped for 30 min for heat dissipation every 1 h to obtain (Ti, V, Nb, Zr, Ta, Hf) C-3.5Ti mixed powder.

[0054] S2. First, the mixture was loaded into a graphite mold for pre-pressing at a pre-pressing pressure of 30 MPa for 60 s; then, the vacuum was evacuated to 40 Pa and the pressure was increased to 40 MPa; then, it was heated from room temperature to 600 °C in 5 min and kept at 600 °C for 10 min; then, it was heated from 600 °C to 1700 °C at a heating rate of 100 °C / min and kept at this temperature for 10 min. The mixture was cooled in the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain (Ti, V, Nb, Zr, Ta, Hf)C-3.5Ti high entropy ceramics.

[0055] The (Ti, V, Nb, Zr, Ta, Hf)C-3.5Ti high entropy ceramic sample was ground and polished for microstructure and performance testing. The density was 98.2%, the hardness was 21.3 GPa, and the toughness was 7.6 MPa m 1 / 2 .

[0056] Taking Example 1, Example 2, and Example 3 as examples, the high entropy ceramics all contain a certain amount of oxide phases. When the sintering temperature is 1600 ° C, the (TiVNbZr)C-1Ti high entropy ceramic sintered body contains a variety of FCC structure solid solution phases. Increasing the sintering temperature and increasing the amount of Ti added can promote the solid solution between metal carbides. Taking Example 7 as an example, there are crack deflection, bridging, branching, and dimples in the high entropy ceramic, which are all the reasons for its high toughness.

[0057] It can be seen from Examples 1-6 that the mechanical alloying time, Ti content, and sintering temperature have a great influence on the performance of the high entropy ceramics prepared in the present invention. It can be seen from Examples 1 and 2 that as the sintering temperature increases from 1600 ° C to 1700 ° C, the hardness of (Ti, V, Nb, Zr)C-1Ti high entropy ceramics increases and the toughness decreases slightly. It can be seen from Examples 5 and 6 that the mechanical alloying time increases from 10 h to 30 h, and the hardness of (Ti, V, Nb, Zr, Ta, Hf)C-1Ti high entropy ceramics is greatly improved. It can be seen from Examples 6 and 7 that as the amount of Ti added increases, the hardness of (Ti, V, Nb, Zr, Ta, Hf)C-Ti high entropy ceramics decreases and the toughness increases, and (Ti, V, Nb, Zr, Ta, Hf)C-3.5Ti high entropy ceramics have higher toughness.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some or all of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A new type of carbide high entropy ceramic, characterized in that: A high-entropy ceramic material with carbon vacancies is prepared in one step by in-situ generating vacancies by adding metallic Ti; the high-entropy ceramic is designed with a composition according to the molar ratio of TiC:VC:NbC:ZrC:Ti=1:1:1:1:x(x=1, 2.5), TiC:VC:NbC:ZrC:TaC:HfC:Ti=1:1:1:1:1:1:x(x=1, 2.5, 3.5).

2. A method for preparing the novel carbide high entropy ceramic according to claim 1, characterized in that: The steps include: S1. Preparation of mixed powder: The mixed powder was prepared using a planetary ball mill, WC carbide ball mill and WC carbide grinding balls. The materials were weighed and loaded into the ball mill according to the ratio, with a ball-to-material ratio of 20:

1. The air was evacuated from the glove box, filled with argon and 0.2-0.5 ml of alcohol was added. The ball mill speed was 450 r / min and the ball milling time was 10-30 h. S2. Preparation of sintered body: The mixed powder prepared in step S1 is loaded into a graphite mold with a diameter of 10 mm and pre-pressed at a pre-pressing pressure of 30 MPa for 60 s; then spark plasma sintering is performed with a vacuum degree of 40 Pa, a sintering pressure of 40 MPa, a sintering temperature of 1500-1800 °C, a heating rate of 100 °C / min, and a holding time of 10 min; then the temperature is reduced and the pressure is released to obtain a high-entropy ceramic sintered body.

3. The method for preparing the novel carbide high entropy ceramic according to claim 2, characterized in that: All raw material powders have a particle size of 1~3 µm and a purity of >99.5%.

4. The method for preparing the novel carbide high entropy ceramic according to claim 2, characterized in that: The ball milling process of step S1 uses three types of large, medium and small WC carbide balls with diameters of 8 mm, 5 mm and 2 mm, respectively, wherein the mass ratio of the large, medium and small WC carbide balls is 6:3:

2.

5. The method for preparing the novel carbide high entropy ceramic according to claim 2, characterized in that: The specific sintering process in step S2 is: first, slowly apply pressure to the sample to 40-50 MPa; then, evacuate to 40 Pa; then, heat from room temperature to 600 ° C in 5 minutes, and keep at 600 ° C for 10 minutes; then increase the temperature from 600 ° C to 1500-1800 ° C at a heating rate of 30-100 ° C / min, and keep for 10 minutes; cool with the furnace to obtain a blank; perform surface grinding and polishing on the prepared blank to obtain a new carbide high-entropy ceramic material.

Citation Information

Cited By

  • Five-element high-entropy carbide ceramic and preparation method thereof

    CN120965331A

  • High-entropy carbide composite ceramic and preparation method thereof

    CN122102713A